2023
DOI: 10.1177/15459683231168384
|View full text |Cite
|
Sign up to set email alerts
|

Early Subacute White Matter Hyperintensities and Recovery of Language After Stroke

Abstract: Background White matter hyperintensities (WMH) are considered to contribute to diminished brain reserve, negatively impacting on stroke recovery. While WMH identified in the chronic phase after stroke have been associated with post-stroke aphasia, the contribution of premorbid WMH to the early recovery of language across production and comprehension has not been investigated. Objective To investigate the relationship between premorbid WMH severity and longitudinal comprehension and production outcomes in aphas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…Fewer studies ( N = 5) have examined the relationship between WMH burden and aphasia outcomes after stroke. Wright et al ( 2018 ), Johnson et al ( 2022 ), and Vadinova et al ( 2023 ) identified a negative association between the degree of WMH and aphasia outcomes at different stages of recovery. Varkanitsa et al ( 2020 ) also found that a greater amount of WMH is negatively associated with response to language therapy, and a study by Basilakos et al ( 2019 ) also showed that a greater amount of WMH predicts a more rapid decline in language skills in chronic aphasia.…”
Section: Introductionmentioning
confidence: 99%
“…Fewer studies ( N = 5) have examined the relationship between WMH burden and aphasia outcomes after stroke. Wright et al ( 2018 ), Johnson et al ( 2022 ), and Vadinova et al ( 2023 ) identified a negative association between the degree of WMH and aphasia outcomes at different stages of recovery. Varkanitsa et al ( 2020 ) also found that a greater amount of WMH is negatively associated with response to language therapy, and a study by Basilakos et al ( 2019 ) also showed that a greater amount of WMH predicts a more rapid decline in language skills in chronic aphasia.…”
Section: Introductionmentioning
confidence: 99%